2023
DOI: 10.1186/s12989-022-00512-8
|View full text |Cite
|
Sign up to set email alerts
|

Polypropylene nanoplastic exposure leads to lung inflammation through p38-mediated NF-κB pathway due to mitochondrial damage

Abstract: Background Polypropylene (PP) is used in various products such as disposable containers, spoons, and automobile parts. The disposable masks used for COVID-19 prevention mainly comprise PP, and the disposal of such masks is concerning because of the potential environmental pollution. Recent reports have suggested that weathered PP microparticles can be inhaled, however, the inhalation toxicology of PP microparticles is poorly understood. Results Inf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(20 citation statements)
references
References 75 publications
1
19
0
Order By: Relevance
“…Ten micrograms per liter of 70 μm PP-MP significantly reduced the survival rate of zebrafish [ 40 ]. However, few studies have measured the effects of PP-MPs on mammalian and cell models, although PP-MPs contribute to pulmonary inflammation in vivo and affect the level of immune cytokines in vitro [ 41 , 42 ]. Meanwhile, PP-MPs with an average particle size of > 50 μm do not exhibit acute toxicity in rats [ 43 , 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ten micrograms per liter of 70 μm PP-MP significantly reduced the survival rate of zebrafish [ 40 ]. However, few studies have measured the effects of PP-MPs on mammalian and cell models, although PP-MPs contribute to pulmonary inflammation in vivo and affect the level of immune cytokines in vitro [ 41 , 42 ]. Meanwhile, PP-MPs with an average particle size of > 50 μm do not exhibit acute toxicity in rats [ 43 , 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, in another experiment, the ROS production in the mitochondria of A549 cells exposed to 4 mg mL −1 PP (252 nm) significantly increased when compared to the control. 92 Microplastics undergoing weathering in the environment can alter their physicochemical characteristics and subsequent biological behaviours. 93 The conversion of plastic products to MPs exacerbates the harmful effects within cells, increases their surface-to-mass ratio, and allows them to migrate through lipid membranes into the cells.…”
Section: Discussionmentioning
confidence: 99%
“…ERK and JNK were unchanged after chronic stress or CGA treatment. p38MAPK is an important member of MAPK, which is not only involved in the cell cycle, development, differentiation, cell death, senescence, and tumorigenesis, but also acts as a specific serine/threonine kinase to regulate inflammation. , A large number of studies have shown that p38 could activate the NF-κB signaling pathway, thereby causing inflammation in some diseases such as IBD, alcohol-induced hepatic injury, lung inflammation, and Parkinson’s. After SB203580 intervention, the phosphorylation level of p65 was significantly reduced, and the transcription and translation levels of TNF were significantly reduced. The intestinal damage was also significantly reduced.…”
Section: Discussionmentioning
confidence: 99%